Pengaruh Arus Kas Terhadap Financial Distress pada Sektor Infrastruktur yang Terdaftar di BEI - Yuniar, Eka; Andriana, Isni; Taufik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of financial distress of cash flow. The type of data used is secondary data. Data collection techniques in this research used documentation studies and literature studies. The data is obtained from Bursa Efek Indonesia. All financial data used in this research is expressed in Rupiah units. The population in this study is a company sector of infrastructure which are listed in Indonesia Stock Exchange for the period 2018-2022, with a total sample of 110(22x5) companies selected using the method purposive sampling and the grouped into two categories, namely 27 included in the category of financial distress and 83 included in the the category of non financial distress. The data analysis technique used is regression logistic analysis using SPSS verison 2.5 software. The result of the research concluded that operating activities of cash flow has no effect on financial distress, investment activities of cash flow has no effect on financial distress and financing activities of cash flow has a positive effect on financial distress.